2020
DOI: 10.1016/j.jtcme.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the tai chi qigong programme on functional capacity, and lung function in chronic obstructive pulmonary disease patients: A ramdomised controlled trial

Abstract: Although the beneficial effect of exercise on the health of Chronic Obstructive Pulmonary Disease (COPD) patients has been widely demonstrated, that of Tai Chi Qigong (TCQ), as an alternative exercise, has been inconclusive. Therefore, this study aimed to evaluate the effects of combined center-and home-based TCQ on functional capacity and lung function in patients with mildly and moderately severe COPD. A total of 50 patients, with a mild and moderate degree of COPD, were recruited and randomly assigned to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
2
8
0
3
Order By: Relevance
“…The vital capacity of the exercise group increased from 1,941.57 ± 551.9 ml to 2,163.86 ± 635.7 ml. This result was similar to a previous study that found MA dependents showed remarkable improvements in vital capacity after moderate-intensity TC intervention ( 88 , 89 ). TC exercise was also been suggested to normalized BMI in MA users ( 66 ).…”
Section: Discussionsupporting
confidence: 92%
“…The vital capacity of the exercise group increased from 1,941.57 ± 551.9 ml to 2,163.86 ± 635.7 ml. This result was similar to a previous study that found MA dependents showed remarkable improvements in vital capacity after moderate-intensity TC intervention ( 88 , 89 ). TC exercise was also been suggested to normalized BMI in MA users ( 66 ).…”
Section: Discussionsupporting
confidence: 92%
“…Traditional Qigong plays an important role in the rehabilitation of lung function [31] . Through the study of chronic obstructive pulmonary disease (COPD), asthma, pulmonary heart disease, and other pulmonary diseases, it is found that Qigong can improve cardiopulmonary function, relieve anxiety, insomnia, and other symptoms, thereby improving the quality of life [32][33] .…”
Section: Rehabilitationmentioning
confidence: 99%
“…Pengamatan ini didukung juga oleh perbaikan dispnea dan kapasitas latihan. (11),( 16), (19) Studi ini merekomendasikan bahwa Tai chi sebagai terapi alternatif pulmonary rehabilitation dengan kenyamanan yang lebih baik dalam pengobatan pasien PPOK. (11) Selaras dengan studi yang dilakukan oleh chan dkk yang terdiri dari tiga kelompok Tai chi, latihan, dan kontrol.…”
Section: Peningkatan Kekuatan Ototunclassified
“…(16), (22) Kelompok Tai chi Qigong (TCQ) juga menunjukkan peningkatan fungsi paru-paru dengan peningkatan nilai FEV1 pada kelompok Tai chi. (18), (19) Volume ekspirasi paksa dalam 1 detik (FEV1) parameter fungsi paru FEV1, FEV 1 % prediksi dan kekuatan diafragma meningkat pada peserta yang berhasil menyelesaikan program Tai chi enam bulan dibandingkan dengan peserta dalam kelompok kontrol yang hanya menerima perawatan rutin. (22) Meningkatkan 6-minute walk distance (6MWD) Random Control Trial (RCT) dengan single blinded menunjukkan peningkatan 6MWD dan mengurangi skor COPD Assessment Tes (CAT) yang signifikan.…”
Section: Peningkatan Kekuatan Ototunclassified